Agricultural performance and policy in Lebanon - Saade C.; Chatila I. (Food and agricultural policies in the Middle East and North Africa: Egypt, Lebanon, Morocco, Sudan, Tunisia, Turkey, 1994)
This report describes the general macro-economic characteristics of Lebanon, explores the performance of the agricultural sector and identifies some action items that could be implemented to improve the functioning of this important sector. It discusses the main physical, human and macro-economic characteristics of Lebanon, and explored the trends observed through the main economic indicators of the past few years. Also provided was a detailed description of the decomposition of the agricultural sector which included land distribution, technology use, infrastructure, productivity, farm gate and retail prices, and value added ratios for different crops in 1988. The major deficiency in Lebanon is the extremely limited role that the public sector plays in the development of the agricultural sector and in the enhancement of the sector's role in the national economy. It seems that a restructuring and rehabilitation of the Ministry of Agriculture is required in order to render it an efficient and effective policy making body that will be engaged in the development of the agricultural sector. The Ministry of Agriculture can play that role if provided with adequate facilities and qualifies personnel. It will also require technical assistance and equipment to assist in its planning and operational functions. In addition, efficient functioning of the National Bank of Agricultural Development is an urgent necessity with regard to agricultural credit. This should be accompanied by land reclamation projects, the rehabilitation and construction of agricultural roads, reservoir construction, and the purchase of agricultural machines. When implemented, these measures will provide the foundation for the continued development of this vital sector of the economy into the coming century.
Workshop on Food and Agricultural Policies in the Middle East and North Africa, 1993/07/05-07, Tunis (Tunisia)